Stress before and during pregnancy increased risk antepartum depression (Faculty of Medicine Universitas Indonesia, 2003)
This paper presents the risk of antepartum depression (APD) among pregnant women. In particular stress before pregnancy, stress during pregnancy, marital relationship, social support, husband's mental status and monthly expenditure. The subjects consisted of 580 pregnant women in the third trimester, who attended antenatal care at the Department of Obstetrics of the Persahabatan Hospital Jakarta from November 1, 1999 to August 15, 2001. Antepartum depression was screened by a psychiatrist using the Edinburgh Postnatal Depression Scale (EPDS). Information on demographic and personal characteristics were collected from fill-in form. Through this form, the respondent gave information on stress before and during pregnancy, and from questionnaires Kuestioner Dukungan Sosial (KDS), Kesesuaian Hubungan Suami Istri (KHSI) and the Symptom Check List-90 (SCL-90) information about social support, marital relationship, and husband's mental status were collected respectively. The prevalence of APD was 18%. Antepartum depression and non-antepartum depression were similar in terms of age groups, level of education, occupations, monthly expenditures, number of pregnancies, number of children, number of deliveries, physical health condition, and history of premenstrual syndromes. Pregnant women with stress before pregnancy had a two-fold risk of APD [adjusted odds ratio (OR)=2.04; 95% confidence intervals (CI): 1.12-3.74] compared to pregnant women without stress before pregnancy. In addition, when compared to pregnant women without stress during pregnancy, those with stress during pregnancy had 2.2-fold risk of developing APD (adjusted OR=2.13, 95% CI: 1,27-3,74). In conclusion, stress before and during pregnancy increased the risk antepartum depression. Therefore, attention should be paid to pregnant women with these risk factors.